Analysis of cognitive abilities measured in a laboratory-controlled 360° simulation in soccer - Heilmann, F.; Weigel, P.; Wollny, R. (German Journal of Exercise and Sport Research, 2021)
Soccer, which is characterized by a very high pace and a short possession time, requires players who are well trained in cognitive abilities. The aim of the study was to quantify cognitive abilities and the improvements in cognitive measures in a laboratory-controlled 360° simulation setting. In all, 82 male youth soccer players (4 age groups) were examined with a pre-/posttest design with an e-training intervention in a unique 360° simulation tool (SoccerBot360 [Umbrella Software Development GmbH, Leipzig, Germany]). The cognitive abilities, especially executive functions, were measured using cognitive tests (Stroop number test, Corsi Block test, Anticipation tests, Choice Reaction test) modified for the 360° simulation to evaluate executive functions and anticipation. The analyzed soccer players showed significant positive changes in cognitive tests from pre- to posttest and significant group effects. The changes in the cognitive test values are not exclusively due to the additional training in the simulation. Nevertheless, the results show significant differences between the four age groups in cognitive abilities and their development.